"Grandiosos Batuques" Tensões, arranjos e experiências coloniais em Moçambique (1890-1940) - Pereira, Matheus (Imprensa de História Contemporânea, 2020)
The word "batuque" (drums) has a multiple history. In general, until today, it is used to name different musical performances and practices produced by Africans or Afro-descendants. This book investigates the historical processes around the "batuques" during the Portuguese early colonialism in Lourenço Marques - currently Maputo - and in southern Mozambique (1890-1940). The categories forged by Portuguese colonial discourses were not able to grasp the multiplicity of experiences of African populations and their practices. Through theoretical and methodological Social History framework, perspectives based on the history "from below" and microhistory research in archives, the "batuques" are, in this book, an object of investigation and a privileged window to analyze resistance, tensions and daily arrangements of those who were subordinated by the Portuguese colonizing power in the region.